Interventions for reducing caregiver burden in chronic dyspnea: a meta-analysis - Liu, Fang; Zhang, Han; Li, Shihan; Wang, Xianshan; Long, Xiaoqing; Liu, Yang (Frontiers in Public Health, 2025)
BackgroundCaregivers of patients with chronic respiratory diseases, such as heart failure, chronic obstructive pulmonary disease, and asthma, often experience significant physical, emotional, and psychological strain. This study aims to evaluate the effectiveness of various interventions designed to reduce caregiver burden and improve caregiver well-being.DesignMeta-analysis of randomized controlled trials (RCTs).MethodsA comprehensive literature search was conducted across multiple electronic databases, identifying randomized controlled trials (RCTs) that assessed interventions aimed at reducing caregiver burden in caregivers of chronic dyspnea patients. A total of 25 RCTs, involving 2,425 participants, were included. The included studies evaluated a variety of interventions, including psychological support, education programs, and physical activity. Data were extracted and analyzed using standardized mean differences (SMD) to assess intervention effects, with heterogeneity and publication bias considered.ResultsA total of 25 RCTs involving 2,425 participants were included in the meta-analysis. Interventions significantly reduced caregiver burden (SMD = −0.65, 95% CI −0.96 to −0.34) with notable heterogeneity (I2 = 82.7%). Subgroup analysis showed a more pronounced reduction in studies conducted in Asia (SMD = −0.80). Improvements were also observed across caregiver burden categories, with the most significant reduction in social burden (SMD = −1.07). Family function improved (SMD = 0.53), but no significant change in social support (SMD = 0.55) or quality of life (SMD = 0.16) was found. Anxiety (SMD = −0.28) showed no significant reduction. Stress (SMD = −0.59) and depression (SMD = −0.45) were significantly reduced. Sensitivity analysis confirmed the robustness of the results.ConclusionInterventions significantly reduce caregiver burden, particularly in emotional, physical, and social aspects, with improvements in family function, stress, and depression. However, no substantial changes were observed in anxiety or quality of life. The evidence quality is moderate, and future studies should focus on improving methodological rigor and exploring long-term effects.Tweetable abstractCaregivers of chronic respiratory disease patients face significant strain. Our meta-analysis of 25 RCTs (2,425 participants) found that interventions significantly reduce caregiver burden, especially in emotional, physical, and social aspects, improving family function, stress, and depression. However, anxiety and quality of life showed no substantial changes. Future research should focus on long-term effects and methodological rigor.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251034352.